Weak degassing from remote Alaska volcanoes characterized with a new airborne imaging DOAS instrument and a suite of in situ sensors - Kern, Christoph; Kelly, Peter J. (Frontiers in Earth Science, 2023)
Gas emissions from volcanoes occur when volatile species exsolve from magmatic and hydrothermal systems and make their way to the surface. Measurements of emitted gases therefore provide insights into volcanic processes. On 16 July 2021, we made airborne measurements of weak gas plumes emitted from four remote Alaska volcanoes: Iliamna Volcano, Mount Douglas, Mount Martin, and Mount Mageik. Integrated into a small fixed-wing aircraft, a new Imaging DOAS instrument was used to map the spatial extent of SO2 plumes as they drifted downwind. The Imaging DOAS simultaneously measures SO2 column density along 48 individual viewing directions oriented in a swath above or below the aircraft. Individual measurements have a comparable precision and sensitivity to conventional Mobile DOAS instruments, and thus provide high resolution 2D imagery of the volcanic plumes and allow calculation of limited emission rate time series information. Although zenith-facing DOAS measurements achieve greater accuracy and are performed here, the application of the Imaging DOAS in a nadir-facing setup is also discussed and compared to satellite observations made in similar geometries. Also onboard the aircraft, a suite of electrochemical and optical sensors measured the relative abundances of the six major volcanic volatile species H2O, CO2, SO2, H2S, HCl, and HF as the aircraft passed through the plumes. Mean SO2 emission rates of 90 ± 10, 20 ± 3, and 13 ± 3 t/d were measured at Iliamna Volcano, Mount Douglas, and Mount Martin, respectively. SO2 emissions were below the DOAS detection limit at Mount Mageik but CO2 and H2S could be measured with the in situ sensors. The information gleaned from these measurements was used to assess and compare activity at these volcanoes, all of which were found to be in a state of background degassing but whose emissions pointed to different source conditions ranging from mixed magmatic-hydrothermal to purely hydrothermal in character. Additional measurements at Mount Spurr, Redoubt Volcano, and Augustine Volcano failed to detect the very weak gas concentrations downwind of these persistently degassing vents.